Validation of Montreal Cognitive Assessment-Basic in a sample of elderly Egyptians with neurocognitive disorders - Saleh, Alia Adel; Alkholy, Rasha Saad Abd El Hamid Ali; Khalaf, Ola Osama; Sabry, Noha Ahmed; Amer, Hanan; El-Jaafary, Shaimaa; Khalil, Mohamed Abd El Fatah (Aging & mental health, 2019)
Background and Objectives: Montreal Cognitive Assessment-Basic (MoCA-B) is a modified version of the MoCA that is especially suitable for use in elderly subjects with low education. The Authors translated the tool into Arabic and they aimed at validation of this tool in a sample of elderly Egyptians. Methods: The study included 93 patients, 60 years and older, fulfilling the DSM-5 criteria of Mild Neurocognitive Disorder (NCD) (39 patients) and Major Neurocognitive Disorder (54 patients) that were compared to 112 community dwelling elder subjects. All subjects were assessed using the MoCA-B, Mini-Mental State Examination (MMSE), and the Clinical Dementia Rating Scale (CDR) in addition to the required laboratory and radiological investigations. Results: MoCA-B demonstrated good internal consistency (Cronbach's alpha = 0.915) and content validity in discrimination between normal and diseased subjects. It showed superior sensitivity and specificity when compared to MMSE in screening for Mild NCD (AUC MoCA-B = 0.988 versus MMSE = 0.939). The recommended cut-off was 21/22 with sensitivity of 92.5% and specificity of 98.2% for detecting Mild NCD and 16/17 with sensitivity of 90.7% and specificity of 97.4% for detecting Major NCD (dementia). Conclusion: The Arabic MoCA-B is a valid cognitive assessment tool in elderly Egyptian subjects.